THE USE OF PROJECT BASED LEARNING METHOD IN DEVELOPING STUDENTS' CRITICAL THINKING - Iskandar, Iskandar; Mulyati, Sri (Universitas Kuningan, 2019)
This research aims to determine the difference of students' critical thinking ability between class which get Project Based Learning (PjBL) method and expository method. The method use experimental method with factorial design 2x2. The research subjects are class X-IPS 1 as an experimental class consists of 32 students and class X-IPS 2 as a control class consists of 32 students. The data collection techniques use test and questionnaires. While, the data analysis technique uses two way Anova. From the result of data analysis, PjBL method is more effective in improving students’ critical thinking ability compared with expository method. However, there is a difference in critical thinking skills, where students with high motivation levels are more effective than students with low motivation. For students who have high motivation but use PjBL method, it is better when compared with students who have high motivation but use expository methods in the control class. There is an interaction between learning methods with learning motivation in affecting the students’ critical thinking ability. Therefore, it is recommended for teacher to use PjBL method on cooperative material. In PjBL method, teachers play an important role in the implementation of the learning process for it requires mastery of materials and good class management and students should actively participate in project execution activities to make learning more meaningful.